Requirement of direct contact between chondrocytes and macrophages for the maturation of regenerative cartilage - Kengo Kanda (Nature Portfolio, 2021)
Abstract Regenerative cartilage prepared from cultured chondrocytes is generally immature in vitro and matures after transplantation. Although many factors, including host cells and humoral factors, have been shown to affect cartilage maturation in vivo, the requirement of direct cell–cell contact between host and donor cells remains to be verified. In this study, we examined the host cells that promote cartilage maturation via cell–cell contact. Based on analysis of the transplanted chondrocytes, we examined the contribution of endothelial cells and macrophages. Using a semiclosed device that is permeable to tissue fluids while blocking host cells, we selectively transplanted chondrocytes and HUVECs or untreated/M1-polarized/M2-polarized RAW264.7 cells. As a result, untreated RAW264.7 cells induced cartilage regeneration. Furthermore, an in vitro coculture assay indicated communication between chondrocytes and RAW264.7 cells mediated by RNA, suggesting the involvement of extracellular vesicles in this process. These findings provide insights for establishing a method of in vitro cartilage regeneration.